Based Smart Room Prototype Internet of Things (Iot) Using Nodemcu (International Journal of Psychosocial Rehabilitation, 2020)
The automatic control system of electronic devices in the room is one solution to create comfortable room conditions. Smart room systems based on the Internet of Things can create automation features for electronic devices in the room and also allow users to control electronic devices from the user interface without having to physically touch the device. Control of electronic devices that are often used today are integrated with mobile devices / smartphones.The purpose of this study is to design an automatic room control system to facilitate human activities in the home such as turning on and off fans and lights using Android devices as a control and using Wifi esp8266 as a communication tool. In application system developmentsmart roomweb-based using the PIECES analysis method, and extreme programming development methods and system design with UML diagrams. The results of this study indicate that the Android smartphone application can replace the function of the control switch of home room appliances. Thus the use of a prototype Smart room system based on IoT (Internet of Things) using nodemcu can simplify human work, because it is not impossible in the future that everything will be connected with one technological device, namely Android.